Copper(II) and Zinc(II) Complexes with the Clinically Used Fluconazole: Comparison of Antifungal Activity and Therapeutic Potential - Nevena Lj. Stevanović; Ivana Aleksic; Jakob Kljun; Sanja Skaro Bogojevic; Aleksandar Veselinovic; Jasmina Nikodinovic-Runic; Iztok Turel; Miloš I. Djuran; Biljana Đ. Glišić (MDPI AG, 2020)
Copper(II) and zinc(II) complexes with clinically used antifungal drug fluconazole (fcz), {[CuCl2(fcz)2].5H2O}n, 1, and {[ZnCl2(fcz)2]·2C2H5OH}n, 2, were prepared and characterized by spectroscopic and crystallographic methods. The polymeric structure of the complexes comprises four fluconazole molecules monodentately coordinated via the triazole nitrogen and two chlorido ligands. With respect to fluconazole, complex 2 showed significantly higher antifungal activity against Candida krusei and Candida parapsilosis. All tested compounds reduced the total amount of ergosterol at subinhibitory concentrations, indicating that the mode of activity of fluconazole was retained within the complexes, which was corroborated via molecular docking with cytochrome P450 sterol 14α-demethylase (CYP51) as a target. Electrostatic, steric and internal energy interactions between the complexes and enzyme showed that 2 has higher binding potency to this target. Both complexes showed strong inhibition of C. albicans filamentation and biofilm formation at subinhibitory concentrations, with 2 being able to reduce the adherence of C. albicans to A549 cells in vitro. Complex 2 was able to reduce pyocyanin production in Pseudomonas aeruginosa between 10% and 25% and to inhibit its biofilm formation by 20% in comparison to the untreated control. These results suggest that complex 2 may be further examined in the mixed Candida-P. aeruginosa infections.